Archive Information System for Incoming and Outgoing Letters At the Wampu Besitang Irrigation Management Unit - Rezka Hartati; Reza Alamsyah; Harry Pratama Figna (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2021)
Incoming mail is a letter received by a company or agency originating from another party, be it individuals or companies/agencies. While outgoing letter is a letter made/issued by a company or agency to be given to other parties, both to individuals and companies/agencies.. At the Wampu Besitang Irrigation Management Unit, there are difficulties in managing the archiving of incoming and outgoing letters where the administrative section is the part that concerns a lot of data or correspondence. In the process of data collection of incoming and outgoing letters, letters are archived into bundles of incoming and outgoing mail files, this makes paper scattered and the required letters are difficult to obtain, therefore a solution is given by building an Archive Information System for Incoming and Outgoing Letters at the Wampu Besitang Irrigation Management Unit which aims to facilitate the management and processing of incoming and outgoing letters.